Apigenin protects ischemic stroke by regulating intestinal microbiota homeostasis, regulates brain metabolic profile - Li, Jinjian; Xu, Qiaoli; Xu, Xiaoming; He, Wei; Zhang, Hui; Ren, Haoxu; Wang, Yue; Wang, Xu; Zhao, Dexi (Frontiers in Pharmacology, 2025)
Background and ObjectiveIschemic stroke is a cerebrovascular disease with highly incidence. Previous research has demonstrated that apigenin provides protective effects against ischemic stroke. However, it remains unclear whether apigenin can regulate intestinal flora against ischemic stroke.MethodsIn this study, we evaluated the regulatory effects of apigenin on intestinal microbiota using a middle cerebral artery occlusion rat model. The protective impact of apigenin on brain damage in ischemic stroke rats was assessed through Nissl staining, hematoxylin and eosin staining, and immunohistochemistry. Additionally, we employed 16S rRNA sequencing to analyze intestinal contents and utilized non-targeted metabolomics to investigate the effects of apigenin on brain metabolites, thereby exploring its mechanism of action. AMPK levels were detected by Western blot and immunohistochemistry. The kit was used to detect oxidative stress and inflammation.ResultsThe intervention with apigenin resulted in significant alterations in the intestinal flora, characterized by an increase in the abundance of probiotic species and a decrease in harmful flora, alongside notable changes in brain metabolite profiles. This protective effect is attributed to apigenin’s promotion of AMPK expression and enhancement of energy metabolism in the context of ischemic stroke. In addition, apigenin improved oxidative stress and inflammation in ischemic stroke.ConclusionThese findings suggest that apigenin exerts a protective effect on ischemic stroke through the AMPK signaling pathway by modulating intestinal flora and associated metabolites. Consequently, apigenin emerges as a therapeutic candidate warranting further investigation.